2023
DOI: 10.3389/fpubh.2023.1180571
|View full text |Cite
|
Sign up to set email alerts
|

Public health palliative care interventions that enable communities to support people who are dying and their carers: a scoping review of studies that assess person-centered outcomes

Anna Peeler,
Alexandra Doran,
Lee Winter-Dean
et al.

Abstract: BackgroundPublic health palliative care views communities as an integral part of care delivery at the end of life. This community-provider partnership approach has the potential to improve end-of-life care for people who are dying and their carers.ObjectiveTo identify and appraise the current literature related to public health interventions that enable communities to support people who are dying and their carers.MethodsA scoping review was conducted, applying Arksey and O'Malley's methods. Data was extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“… 19 Whilst this is clearly an important factor for improving the quality of clinical care, it may also be helpful to consider the rich potential that these complex and informal networks may provide in terms of developing community capacity to support those at end of life. Indeed, a UK study of urban and rural differences in access to palliative care services recommends that end-of-life care policies and strategies consider differences in settlement types such as rurality 20 ; the findings from both our engagement work and scoping review 16 suggest that strategies to strengthen capacity for community support should also seek to develop tailored solutions that respond to local context.…”
Section: Methodology: Our Community Engagement Strategymentioning
confidence: 97%
See 1 more Smart Citation
“… 19 Whilst this is clearly an important factor for improving the quality of clinical care, it may also be helpful to consider the rich potential that these complex and informal networks may provide in terms of developing community capacity to support those at end of life. Indeed, a UK study of urban and rural differences in access to palliative care services recommends that end-of-life care policies and strategies consider differences in settlement types such as rurality 20 ; the findings from both our engagement work and scoping review 16 suggest that strategies to strengthen capacity for community support should also seek to develop tailored solutions that respond to local context.…”
Section: Methodology: Our Community Engagement Strategymentioning
confidence: 97%
“…To better understand the support needs of communities in underserved rural, coastal and low-income areas at the end of life, SWPPCRP members carried out a scoping review of existing evidence reporting public health palliative care interventions that enable communities to support people who are dying and their carers. 16 We also developed a programme of community engagement to explore:…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to acknowledge that sustaining the partnership at the same level of activity has not been feasible beyond the funded period due to a lack of capacity to provide the necessary administrative infrastructure. In our scoping review, 18 we found that the long-term sustainability of interventions was rarely reported. Interestingly, in 13 of 18 included studies, community members acted as agents to deliver the intervention and in 7 these were paid members of the research team.…”
Section: Future Research and Sustainabilitymentioning
confidence: 93%